Antropolojik didaktik teorisi ve fen öğretimi - (:unkn) unknown (My University, 2009)
1982 yılında, Yves Chevallard tarafından geliştirilen didaktiksel dönüşüm teorisi, daha sonra 1991 yılında antropolojik didaktik yaklaşımına giriş yapılarak genişletilmiştir. Antropolojik didaktik teorisinde didaktik sistemin bir elemanı olan bilgi, bir nesne olarak ele alınmış olup kurum ve bireylerle olan ilişkisi irdelenmiştir. Bu makale, antropolojik didaktik teorisini ve özelliklerini Türk eğitim çevrelerine tanıtmak ve fen öğretimi araştırmalarında kullanılması için bir teorik kapsam oluşturabildiğini göstermek amacıyla yazılmıştır. Makalede, doküman analizi yapılarak öncelikle bu teorinin bileşenleri tanıtılmış, ardından fen öğretiminde kullanılmasına örnek olabilecek bir çalışma üzerinde uygulaması gösterilmiştir.

Theory of Transposition Didactic which was established at 1982 was enlarged with the Anthropological Theory in the 1990’s which was introduced by Y. Chevallard. The anthropological theory is frequently used in didactical researches. The knowledge in the didactical system is object in this theory, its relations to institutions and personnel are quite important. For this purpose, this study presents definitions and concepts specific to the Anthropological Theory in Turkish Education members and shows the positive results of anthropological theory can be used from the studies applying that theory in science areas. In the study, the first section aims to present characteristics what the Anthropological Theory is with documentation analyze; and, the second section also aims to present one research in science education (realized by YILDIRIM in 2008) in order to illustrate the use and the effectiveness of the theory.
Anthropological theory of the didactic and science teaching
Keywords: Eğitim, Eğitim Araştırmaları